A systematic review of primary prevention strategies for sexual violence perpetration - DeGue, Sarah; Valle, Linda Anne; Holt, Melissa K.; Massetti, Greta M.; Matjasko, Jennifer L.; Tharp, Andra Teten (Aggression and violent behavior, 2014)
This systematic review examined 140 outcome evaluations of primary prevention strategies for sexual violence perpetration. The review had two goals: 1) to describe and assess the breadth, quality, and evolution of evaluation research in this area; and 2) to summarize the best available research evidence for sexual violence prevention practitioners by categorizing programs with regard to their evidence of effectiveness on sexual violence behavioral outcomes in a rigorous evaluation. The majority of sexual violence prevention strategies in the evaluation literature are brief, psycho-educational programs focused on increasing knowledge or changing attitudes, none of which have shown evidence of effectiveness on sexually violent behavior using a rigorous evaluation design. Based on evaluation studies included in the current review, only three primary prevention strategies have demonstrated significant effects on sexually violent behavior in a rigorous outcome evaluation: Safe Dates (Foshee et al., 2004); Shifting Boundaries (building-level intervention only, Taylor, Stein, Woods, Mumford, & Forum, 2011); and funding associated with the 1994 U.S. Violence Against Women Act (VAWA; Boba & Lilley, 2009). The dearth of effective prevention strategies available to date may reflect a lack of fit between the design of many of the existing programs and the principles of effective prevention identified by Nation et al. (2003).